DEVELOPMENT OF FORMATIVE ASSESSMENT MODES BY QUIDED-INQUIRY BASED TO FOSTER SELF-REGULATION OF STUDENT’ HIGH SCHOOL - asih sulistia ningrum; Chandra Ertikanto; Undang Rosidin (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The purpose of this research to produce a product of formative assessment model by guided-inquiry based to foster self-regulation of student in physics learning of high school, produce special are: characteristic formative assessment model, practically, benefit, and effectiveness formative assessment model guided-inquiry based to foster self-regulation student’ learning high school in development. The research is a research and development (R&D). Design development use a one-shot case study design. Subject trials is a physics teacher and student in high school. Data collection techniques such as questionnaires and assessment instruments. The results of the formative assessment model guided-inquiry based developement have characteristics of a set of assessments consisting of assessment scenarios, pretest-posttest, self-assessment & peer-assessment sheets and scoring guidelines. The results of the practicality and benefit test show that the formative assessment model is a very practical with amount 91% and very effective with amount 95% for use during physics learning. Furthermore, the results its effectiveness test show that are implementation of a formative assessment model guided-inquiry based is highly effective (n-gain = 0.75) used during physics learning.Keywords: Formative Assessment Model, Guided-Inquiry, Self-Regulation.